STRUCTURE COMMUNITY OF MANGROVE FOREST IN NORTH COASTAL RUPAT ISLAND DISTRICT OF BENGKALIS RIAU PROVINCE - Nasution, Muhammad Rasid; Samiaji, Joko; ', Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in January 2017 in north coastal rupat island district of bengkalis riau province. The purpose of this researches is to determine the structure community of mangroves in rupat island. The method used in the research was transect line method and plot. The result of observation in North Rupat Island showed the existence of mangrove vegetation that comes the 17 species and 7 families. The species of most dominating growth was Rhizophora apiculata has important values and high density than other species was value 288.9 ind/ha. The second of high density was Rhizophora mucronata with value 144.4 ind/ha. So, the species of Rhizophora apiculata and Rhizophora mucronata is the species capable of grow well on each environment in north coastal rupat island district of bengkalis riau province. Researchers also identify zoning mangrove vegetation.Keywords : Rupat Island, Structure Community, Mangroves, Rhizophora1Student of